Grammatical and Lexical Competence of Grade 9 Students in Tanque National High School - Edem, Kristy Love (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the grammatical and lexical competence of Grade 9 students in Tanque National High School during the 2022–2023 school year. Anchored on the Behaviorism, Cognitivism, Constructivism, and Socio-cultural theories of language learning, the study examined learners’ competency levels and determined whether a significant difference existed between grammatical and lexical competence. A descriptive-correlational research design was employed involving 160 Grade 9 students as respondents. Data were collected using a validated researcher-made questionnaire consisting of 40 items, with 20 items each assessing grammatical and lexical competence. The gathered data were analyzed using percentage, weighted mean, and an independent sample t-test. The findings revealed a mean percentage score of 58.6% in lexical competence and 64.8% in grammatical competence, both of which were below the Department of Education’s 75% proficiency benchmark. Statistical analysis further showed no significant difference between grammatical and lexical competence, indicating that the respondents demonstrated comparable proficiency levels in both language domains. The findings suggest that although the students possess basic English language skills, their grammatical and lexical competence remain at a developing level and require improvement. The study recommends integrating grammar and vocabulary instruction through contextualized learning, implementing a remedial English program for learners who fall below the proficiency benchmark, strengthening the explicit teaching of academic vocabulary in the English curriculum, and conducting further studies using qualitative approaches to explore factors affecting learners’ language competence. The study supports Sustainable Development Goal (SDG) 4 – Quality Education by providing evidence to improve English language instruction and learner achievement. It also aligns with SDG 8 – Decent Work and Economic Growth by promoting language competence as a foundation for lifelong learning and future employability. The findings contribute to educational and institutional sustainability by informing instructional improvement, curriculum enhancement, and evidence-based language education practices.